Modalni katapulti: Uvod v filozofsko logiko - Šuster, Danilo (University of Maribor Press, 2023)
Modal Catapults: An Introduction to Philosophical Logic. The first part of the book consists of six philosophical essays where a certain modal argument, modal rule or thesis plays a central role. The discussions include modal logic, multi-valued logics, the combination of epistemic and modal logic, deontic logic and the logic of counterfactual conditionals. The author discusses arguments for fatalism and logical determinism, the modal argument for the incompatibility of freedom and determinism, Fitch’s paradox of knowledge and the problem of moral dilemmas. The central logical theme is the ancient rule: logical consequences are also modal consequences. In the second part, introduction to modal logic, the author follows the classical scheme: modal logic (axiomatic systems) and then the semantics of possible worlds. The author clearly explains the relation between modal theses and conditions on Kripkean frameworks (the accessibility relation), which leads to different systems of modal logic. His treatment is enriched with a critical discussion of controversial propositions ("paradoxes") and connected with the philosophical problems in the first part of the book. The author always clearly presents his view.